1998
DOI: 10.1523/jneurosci.18-23-09996.1998
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Containing Hypocretin (Orexin) Project to Multiple Neuronal Systems

Abstract: The novel neuropeptides called hypocretins (orexins) have recently been identified as being localized exclusively in cell bodies in a subregion of the tuberal part of the hypothalamus. The structure of the hypocretins, their accumulation in vesicles of axon terminals, and their excitatory effect on cultured hypothalamic neurons suggest that the hypocretins function in intercellular communication. To characterize these peptides further and to help understand what physiological functions they may serve, we under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

107
2,475
4
31

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 3,144 publications
(2,666 citation statements)
references
References 49 publications
107
2,475
4
31
Order By: Relevance
“…Renewed interest in the hypothalamus has emerged due to the discovery of the hypocretinergic system which has been suggested to be involved in the control of motor activity, sleep and wakefulness (reviewed by (Siegel, 2004, Sutcliffe and de Lecea, 2002, Taheri, et al, 2002). MCHergic neurons are intermingled with the hypocretinergic neurons in the hypothalamus and their projections are strikingly similar (Bayer, et al, 2002, Bittencourt, et al, 1992, Guan, et al, 2002, Peyron, et al, 1998, Skofitsch, et al, 1985; this anatomical data suggest that the MCHergic neurons may also contribute to the regulation of motor activity, sleep and waking functions. However, very few reports examined the role of MCH in relation to these functions.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Renewed interest in the hypothalamus has emerged due to the discovery of the hypocretinergic system which has been suggested to be involved in the control of motor activity, sleep and wakefulness (reviewed by (Siegel, 2004, Sutcliffe and de Lecea, 2002, Taheri, et al, 2002). MCHergic neurons are intermingled with the hypocretinergic neurons in the hypothalamus and their projections are strikingly similar (Bayer, et al, 2002, Bittencourt, et al, 1992, Guan, et al, 2002, Peyron, et al, 1998, Skofitsch, et al, 1985; this anatomical data suggest that the MCHergic neurons may also contribute to the regulation of motor activity, sleep and waking functions. However, very few reports examined the role of MCH in relation to these functions.…”
Section: Discussionmentioning
confidence: 70%
“…In hamsters and rats, MCHergic neurons are intermingled with hypocretinergic neurons and make numerous synaptic contacts with these cells (Bayer, et al, 2002, Guan, et al, 2002, Khorooshi and Klingenspor, 2005. The hypocretinergic system has an anatomical organization similar to the MCHergic system (Peyron, et al, 1998), and it has been proposed to be involved in the regulation of behavioral states; deficits in this system have been associated with narcolepsy/cataplexy (Siegel, 2004, Sutcliffe and de Lecea, 2002, Taheri, et al, 2002. In the present report, as a foundation for furthering understanding of the function of the MCHergic system and its interactions with the hypocretinergic system, we determined the location of the neuronal somata of MCH-containing neurons and their anatomical relationship with the hypocretinergic system in the cat.…”
Section: Introductionmentioning
confidence: 99%
“…The hypocretin-producing neurons in the hypothalamus receive direct input from the SCN (the circadian rhythm clock) and project to the posterior hypothalamus (tuberomammillary nucleus [TMN]-histamine), basal forebrain (cholinergic vigilancewake area), thalamus, locus caeruleus and dorsal raphe neucleus (norepinephrine and serotonin REM off cells), LDT, and PRF (cholinergic REM-on cells and muscle atonia) [30], [31] . In accordance with circadian rhythm control of hypocretin levels (through SCN input), their concentration is highest during the waking period.…”
Section: Hypocretinmentioning
confidence: 99%
“…In addition to the locus coeruleus, the lateroanterior hypothalamic nucleus, ventromedial hypothalamic nucleus, amygdalohippocampal area, and dorsal and median raphe highly express OX1R. Immunohistochemical studies have shown that orexinimmunoreactive fibers and terminals are richly distributed in these brain sites (15,16,17). It is therefore speculated that the site of action of orexin-A to stimulate gastric acid secretion should be in the brain nuclei that express OX1R because the orexin-A-induced stimulation of gastric acid should be mediated through the action of OX1R as shown in this study.…”
Section: Page 13mentioning
confidence: 99%